Are there differences between macrocyclic gadolinium contrast agents for brain tumor imaging? Results of a multicenter intraindividual crossover comparison of gadobutrol with gadoteridol (the TRUTH study) - Maravilla, K R; Smith, M P; Vymazal, J; Goyal, M; Herman, M; Baima, J J; Babbel, R; Vaneckova, M; Žižka, J; Colosimo, C; Urbańczyk-Zawadzka, M; Mechl, M; et al. (AJNR. American journal of neuroradiology, 2015)
BACKGROUND AND PURPOSE: Gadobutrol (Gadavist) and gadoteridol (ProHance) have similar macrocyclic molecular structures, but gadobutrol is formulated at a 2-fold higher (1 mol/L versus 0.5 mol/L) concentration. We sought to determine whether this difference impacts morphologic contrast-enhanced MR imaging. MATERIALS AND METHODS: Two hundred twenty-nine adult patients with suspected or known brain tumors underwent two 1.5T MR imaging examinations with gadoteridol or gadobutrol administered in randomized order at a dose of 0.1 mmol/kg of body weight. Imaging sequences and T1 postinjection timing were identical for both examinations. Three blinded readers evaluated images qualitatively and quantitatively for lesion detection and for accuracy in characterization of histologically confirmed brain tumors. Data were analyzed by using the Wilcoxon signed rank test, the McNemar test, and a mixed model. RESULTS: Two hundred nine patients successfully completed both examinations. No reader noted a significant qualitative or quantitative difference in lesion enhancement, extent, delineation, or internal morphology (P values = .69-1.00). One hundred thirty-nine patients had at least 1 histologically confirmed brain lesion. Two readers found no difference in the detection of patients with lesions (133/139 versus 135/139, P = .317; 137/139 versus 136/139, P = .564), while 1 reader found minimal differences in favor of gadoteridol (136/139 versus 132/139, P = .046). Similar findings were noted for the number of lesions detected and characterization of tumors (malignant/benign). Three-reader agreement for characterization was similar for gadobutrol (66.4% [κ = 0.43]) versus gadoteridol (70.3% [κ = 0.45]). There were no significant differences in the incidence of adverse events (P = .199). CONCLUSIONS: Gadoteridol and gadobutrol at 0.1 mmol/kg of body weight provide similar information for visualization and diagnosis of brain lesions. The 2-fold higher gadolinium concentration of gadobutrol provides no benefit for routine morphologic imaging.
Keywords: dospělí; Magnetic Resonance Imaging; Organometallic Compounds; Female; klinické křížové studie; Adult; ženské pohlaví; neurozobrazování; nádory mozku; lidé; organokovové sloučeniny; Heterocyclic Compounds; magnetická rezonanční tomografie; Cross-Over Studies; heterocyklické sloučeniny; Middle Aged; Male; Aged; kontrastní látky; gadolinium; Brain Neoplasms; lidé středního věku; senioři; mužské pohlaví; Contrast Media; Neuroimaging; Gadolinium; Humans